Israel : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
The study shows that the Israeli economy has emerged unscathed from the global financial crisis. The first part of the study outlines the relationship between risk and Israel's macroeconomic performance, estimated through a regression analysis. The second part of the study focuses on macrofinancial policies to cope with macrofinancial risk, with special emphasis on monetary and fiscal intervention. The study shows that stress testing and CCA analysis play a role in supervisory work; they complement and can inform each other in critical areas.